If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4B + 3B + -1 = 27 Reorder the terms: -1 + 4B + 3B = 27 Combine like terms: 4B + 3B = 7B -1 + 7B = 27 Solving -1 + 7B = 27 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 7B = 27 + 1 Combine like terms: -1 + 1 = 0 0 + 7B = 27 + 1 7B = 27 + 1 Combine like terms: 27 + 1 = 28 7B = 28 Divide each side by '7'. B = 4 Simplifying B = 4
| x-2=2+x-x | | (2x-3)(x+8)=126 | | 0.10n+0.05(2n)+0.25(n-3)=4.5 | | 42-12=5(x-7) | | 12=-4(-6v-3) | | 19=v/15= | | 2n-1+3n+4= | | 0.10n+0.05(2n)+0.25(n-3)=11.10 | | -16+y=-6y | | -3=×/5 | | 18x^6y^2-12x^5y^4=0 | | -9=n+1 | | 2=4+3n-5n | | 2X^2-10X+0=0 | | 4t^2-13t-75=0 | | 15x^7y^3-20x^5y^4=0 | | x^3-4x^2+4x=f(x) | | f(-6)=3x^2 | | 3a(4b-7)= | | 4(x+5)=6x+19-2x+1 | | 10x^3y^4-15x^5y^3=0 | | 40x^5y^4-10x^7y^3=0 | | 25a^3b^4-15a^5b^3=0 | | y=0.50(-3)+5.00 | | 4/(x-2)-2/(x)=14/(x^2-2x) | | 6x^2-y^2=12 | | 1/(x)^(2/3)=1 | | 6x+29x-3=7(5x+4) | | 12x^3y^4-18x^5y^3=0 | | 7x+43x-5=10(5x+5) | | 8-2x=2x+-8 | | -3ab(4a^2-2b-5ab^2)+6ab^2= |